Ethnogeographic Aspects of Social Life About Problems (Global Scientific Review, 2023)
Has the natural social environment formed over the centuries, passed the test of time, raised national values, traditions, experience, skills and qualifications combined with features such as oriental gratitude, contentment, extravagance, fear of extravagance? forms the basis of ethnoecological culture. So far, this period has valued culture more in terms of itself and its environment. It is true that this kind of physical social and economic development serves to express more correctly, it helps the technical and technological development. However, in this research, the ethnoecological culturalization of the traditions, skills and skills of our people in carrying out from nature was sought